2008
DOI: 10.2340/16501977-0233
|View full text |Cite
|
Sign up to set email alerts
|

Systematic co-operation between employer, occupational health service and social insurance office: A 6-year follow-up of vocational rehabilitation for people on sick-leave, including economic benefits

Abstract: The study group had 5.7 fewer days on sick-leave per month and person over the 6-year period (p=0.003). The estimated average economic benefit of the intervention was euro36,600 per person over the 6-year period. In conclusion, those who received systematic co-operation in vocational rehabilitation had fewer days on sick-leave than their "treatment-as-usual" peers. This effect persisted over 6 years, generating substantial net economic gains for society.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
12
0
1

Year Published

2010
2010
2018
2018

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(14 citation statements)
references
References 23 publications
1
12
0
1
Order By: Relevance
“…Furthermore, the opinions of our participants are completely anonymous and cannot be linked to specific individuals or the reintegration services where these professionals work. Our data are consistent with other studies that found that commitment of stakeholders should be stimulated to achieve successful RTW (43,44). According to the findings in this study, our participants are important external RTW stakeholders who act as motivators for employees on long-term sick leave.…”
Section: Dekkers-sánchez Et Alsupporting
confidence: 81%
“…Furthermore, the opinions of our participants are completely anonymous and cannot be linked to specific individuals or the reintegration services where these professionals work. Our data are consistent with other studies that found that commitment of stakeholders should be stimulated to achieve successful RTW (43,44). According to the findings in this study, our participants are important external RTW stakeholders who act as motivators for employees on long-term sick leave.…”
Section: Dekkers-sánchez Et Alsupporting
confidence: 81%
“…The remaining 4 studies (4%) all used ad hoc approaches that (41, 45-48, 51, 56-58, 60, 62, 64, 66, 68, 70, 72-75, 79, 81, 83, 84, 87-90, 92, 93, 95, 97, 98, 100-102, 105, 107-110, 113, 117-125) North-America 34 (39, 40, 43, 44, 50, 52-55, 59, 61, 63, 65, 69, 71, 76, 80, 82, 85, 86, 91, 94, 96, 99, 103, 106, 111, 112, 114-116, 126- (39, 41, 42, 44, 45,49,50,(52)(53)(54)(55)59,60,67,68,70,71,76,77,82,87,95,115, 128) Inferred: 19 (40, 43, 46,57,61,63,65,80,86,91,92,94,96,103,111,116,(125)(126)(127)56,62,64,66,69,72,73,75,78,79,81,(83)(84)(85)…”
Section: Productivity Estimation Methodsmentioning
confidence: 99%
“…Measure for reduced productivity at work/ while working 31 (39, 41-44, 56, 60-65, 69, 70, 72, 77, 82, 87, 89, 94, 95, 98, 103, 104, 114, 115, 118, 119, 123, 124, 128) Source presenteeism Employee survey 18 (41, 44,56,62,64,69,72,82,87,89,94,95,98,104,115,118,119, 123) Simulated / assumptions 7 (39, 43, 44,103,114,124, 128) Previous studies 6 (42,60,61,63,65,70) Firm data 1 (115) Employer survey 1 (77) Survey/instrument presenteeism 56,62,69,82,94,95,118,119,123) Days (unspecified) 49 (39, 40, 42, 46,49,(51)(52)(53)(54)58,60,62,64,66,71,72,74,75,(77)(78)…”
Section: Presenteeismmentioning
confidence: 99%
“…A Swedish study showed the clear inancial and operational beneits of systematic and solution-oriented co-operation for all parties involved [50].…”
Section: External Stakeholdersmentioning
confidence: 99%